2021
DOI: 10.1155/2021/8811396
|View full text |Cite
|
Sign up to set email alerts
|

CMV Pancreatitis in an Immunocompromised Patient

Abstract: Introduction. Cytomegalovirus (CMV) is a common double-stranded DNA (dsDNA) virus affecting a large majority of the world’s population. In immunocompetent patients, CMV infection can range anywhere from an asymptomatic course to mononucleosis. However, in the immunocompromised patient, prognosis can be deadly as CMV can disseminate to the retina, liver, lungs, heart, and GI tract. We present a case of CMV pancreatitis afflicting an immunocompromised patient. Case Summary. A 45-year-old Hispanic female with no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…[7][8][9] Although CMV is known to affect many organs in immunocompromised patients, few cases of pancreatitis have been reported. 10,11 In our case, these 2 rare pathologies were observed together in PET/CT imaging.…”
supporting
confidence: 50%
“…[7][8][9] Although CMV is known to affect many organs in immunocompromised patients, few cases of pancreatitis have been reported. 10,11 In our case, these 2 rare pathologies were observed together in PET/CT imaging.…”
supporting
confidence: 50%
“…Studies have shown that a wide spectrum of viruses, such as HIV, severe acute respiratory syndrome coronavirus 2, hepatotropic virus, Cytomegalovirus, Ebola virus, Coxsackie virus, Paramyxovirus, Herpes Simplex virus and Varicella Zoster virus, as well as tuberculosis, Mycobacterium and Toxoplasmosis, can infect pancreatic cells and present clinical manifestations ranging from mild to severe. [19][20][21][22][23][24][25][26] Microorganisms in the pancreas of PLWH have a unique composition compared to the pancreas of a healthy population. Early studies of necropsy AIDS patients have demonstrated the presence of microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, the immunocompromised status of patients can indeed play a role in the development and severity of viral-induced acute pancreatitis. Immunocompromised individuals, such as those with weakened immune systems due to conditions like varicella zoster virus/cytomegalovirus, organ transplantation, or immunosuppressive therapy, may be more susceptible to viral infections ( Oku et al, 2005 ; Picod et al, 2017 ; Ahmad et al, 2021 ). Viruses that can cause pancreatitis may take advantage of the compromised immune response, leading to more severe and prolonged episodes of inflammation in the pancreas.…”
Section: Mechanism Of Viral Associated Pancreatitismentioning
confidence: 99%